Business Travelers' Risk Perception of Infectious Diseases: Where Are the Knowledge Gaps, and How Serious Are They?. Issue 1 (4th December 2012) - Wynberg, Elke; Toner, Sharyn; Wendt, Judy K.; Visser, Leo G.; Breederveld, Daan; Berg, Johannes
<x xml:space="preserve">Abstract</x> Background Many studies have explored the risk perception of frequent business travelers (FBT) toward malaria. However, less is known about their knowledge of other infectious diseases. This study aimed to identify knowledge gaps by determining the risk perception of FBT toward 11 infectious diseases. Methods Our retrospective web‐based survey assessed the accuracy of risk perception among a defined cohort of FBT for 11 infectious diseases. We used logistic regression and the chi‐square test to determine the association of risk perception with source of travel advice, demographic variables, and features of trip preparation. Results Surveys were returned by 63% of the 608 self‐registered FBT in Rijswijk, and only the 328 completed questionnaires that adhered to our inclusion criteria were used for analysis. The majority (71%) sought pre‐travel health advice and used a company health source (83%). Participants seeking company travel health advice instead of external had significantly more accurate risk knowledge (p = 0.03), but more frequently overestimated typhoid risk (odds ratio = 2.03; 95% confidence interval = 1.23–3.34). While underestimation of disease risk was on average 23% more common than overestimation, HIV risk was overestimated by 75% of FBT. Conclusions More accurate knowledge among FBT seeking company health advice demonstrates that access to in‐company travel clinics can improve risk perception. However, there is an obvious need for risk knowledge improvement, given the overall underestimation of risk. The substantial overestimation of HIV risk is probably due to both public and in‐company awareness efforts. Conversely, typhoid risk overestimation was statistically associated with seeking company health advice, and therefore specifically reflects the high focus on typhoid fever within Shell's travel clinic. This study serves as a reminder that a knowledge gap toward infectious diseases besides malaria still exists. Our article will explore the future requirements for more targeted education and research among FBT in companies worldwide.